Mild Head Injury and Stroke - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2003)
Five children, ages 1 to 6 years (4 female, 1 male), who suffered acute hemiparesis due to ischemic stroke and striatocapsular infarction within a few minutes to 6 hours following a mild head injury are reported from the Institute of Child Health and Great Ormond Street Hospital, London, UK.